Does Social Support Buffer the Association Between Stress Eating and Weight Gain During the Transition to College? Differences by Gender. (May 2017) - Darling, Katherine E.; Fahrenkamp, Amy J.; Wilson, Shana M.; Karazsia, Bryan T.; Sato, Amy F.
This study sought to examine whether social support moderates the relationship between stress eating and body mass index (BMI) change over the freshman year in males and females. This longitudinal study included 70 college students (72.9% female; M age = 18.23) who completed self-reported measures of stress eating and perceived social support, with objective height and weight measurements collected. Among males, social support moderated the relationship between stress eating and BMI change. Among males, social support may serve as a buffer against the impact of stress eating on weight gain during the freshman year of college.